2002
DOI: 10.1063/1.1483929
|View full text |Cite
|
Sign up to set email alerts
|

Electron conduction through quasi-one-dimensional indium wires on silicon

Abstract: Electron conduction through quasi-one-dimensional (1D) indium atomic wires on silicon (the Si(111)-4×1-In reconstruction) is clarified with the help of local structural analysis using scanning tunneling microscopy. The reconstruction has a conductance per square as high as 100 µS, with global conduction despite numerous surface steps. A complete growth of indium wires up to both the surface steps and the lithographically printed electrodes is essential for the macroscopic transport. The system exhibits a metal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
57
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 11 publications
1
57
1
Order By: Relevance
“…Shortly after the first observation of superconducting energy gap by means of scanning tunneling spectroscopy (STS) [1], insitu electrical transport measurements have demonstrated that supercurrents can travel over macroscopic distances in those surface systems [2][3][4]. The finding of the macroscopic supercurrents was unexpected, because the surfaces always have atomic steps that may decouple metallic films grown on the terraces [6,7]. The temperature dependence of the critical current suggests that the supercurrents flow across the atomic steps with the help of the Josephson effect [2].…”
Section: Introductionmentioning
confidence: 99%
“…Shortly after the first observation of superconducting energy gap by means of scanning tunneling spectroscopy (STS) [1], insitu electrical transport measurements have demonstrated that supercurrents can travel over macroscopic distances in those surface systems [2][3][4]. The finding of the macroscopic supercurrents was unexpected, because the surfaces always have atomic steps that may decouple metallic films grown on the terraces [6,7]. The temperature dependence of the critical current suggests that the supercurrents flow across the atomic steps with the help of the Josephson effect [2].…”
Section: Introductionmentioning
confidence: 99%
“…Grooves are visible along step δ, indicating that the superconducting indium layers did not grow up to the step edge. This should result in a weak electronic coupling between the upper and lower terraces [14] and hence in a low J c /J 0 . In contrast, such a structure is nearly absent for step α, which helps to establish a stronger interterrace coupling.…”
mentioning
confidence: 99%
“…Atomic steps are considered to strongly affect electron transport phenomena, because they potentially decouple neighboring surface terraces [12][13][14][15]. This could prevent superconducting currents from running over a long distance.…”
mentioning
confidence: 99%
“…ð8 Â 2Þ phase transition, but also the LT ground-state and its properties remain controversial. While the RT ð4 Â 1Þ phase is a quasi-1D metal [12,16,22], it has been variously suggested that the LT ð8 Â 2Þ phase is metallic, but with a lower density of states at the Fermi level [19,20,23], semimetallic [19], and semiconducting with a fundamental energy gap of 0.1-0.3 eV [15][16][17][18]21]. Most ab initio calculations predict the nanowire ground state to be characterized by the formation of In trimers (cf.…”
mentioning
confidence: 99%